Perlindungan Hukum Wisatawan Menurut Undang-Undang No 10 Tahun 2009 Tentang Kepariwisataan - Muhammad Hamimulloh; Muhammad Ghufron AZ; Dewi Dewi Astutty M (MLJ Merdeka Law Journal, 2021)
This study aims to analysis implementation of Article 20 Letter C of Law No. 10 of 2009 concerning Tourism in Malang Regency and Analysis of Legal Protection and Security of Tourism Service Users in Malang Regency. Research that uses this type of juridical empirical research by conducting research based on laws that is adjusted to experiences that occur in society to better understand and understand law as a set of regulations or positive norms that apply. This research is also called qualitative legal research. The research data were collected by means of field studies and legal materials related to this, then processed and analyzed with a community approach and invitation. The results of this study indicate that people who use tourism services, especially in Malang district, have legal and security guarantees. However, this rule is not used as a reference based on the government in management in Malang Regency. So it is necessary to know that the government is to improve legal protection and security for tourism service users in Malang RegencyDOI: https://doi.org/10.26905/mlj.v2i2.7796